2013
DOI: 10.1021/jz302146m
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Shielding Constants of Heavy Nuclei: Resolving the Enigma of the 119Sn Absolute Shielding

Abstract: We demonstrate that the apparent disagreement between experimental determinations and four-component relativistic calculations of the absolute shielding constants of heavy nuclei is due to the breakdown of the commonly assumed relation between the electronic contribution to the nuclear spin-rotation constants and the paramagnetic contribution to the NMR shielding constants. We demonstrate that this breakdown has significant consequences for the absolute shielding constant of (119)Sn, leading to errors of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 37 publications
10
74
0
Order By: Relevance
“…21 We note that a similar result was later derived in the framework of density-functional theory by Xiao, Zhang, and Liu. 23 In the case of the 119 Sn nucleus, Malkin et al showed that the relativistic correction between the shielding constant and the nuclear spin-rotation constant is highly transferable and large, about 1000 ppm, which amounts to about 25%-30% of the absolute chemical shielding for this fairly light nucleus.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…21 We note that a similar result was later derived in the framework of density-functional theory by Xiao, Zhang, and Liu. 23 In the case of the 119 Sn nucleus, Malkin et al showed that the relativistic correction between the shielding constant and the nuclear spin-rotation constant is highly transferable and large, about 1000 ppm, which amounts to about 25%-30% of the absolute chemical shielding for this fairly light nucleus.…”
Section: Introductionsupporting
confidence: 74%
“…(1) is not valid when a full relativistic description of the spin-rotation and nuclear magnetic shielding constants is considered. 20,21 Indeed, Aucar et al showed that at the four-component relativistic framework, there is no direct relationship between the absolute shielding constant and the nuclear spin-rotation constant, 20 and this finding was further substantiated by a detailed analysis of Xiao and Liu. 22 Through a perturbation analysis, Aucar et al showed that whereas the relativistic spin-orbit corrections are common to both the spin-rotation and the nuclear magnetic shielding constants, relativistic operators probing the electron density close to the nucleus are unique to the shielding constants and do not appear for the spin-rotation constants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them were proposed based on theoretical calculations [7][8][9][10][11][12][13] and others based on a mixture between spin-rotation measurements and theoretical calculations of free atoms.…”
Section: 6mentioning
confidence: 99%
“…7 for model systems HX (X=H,F,Cl,Br,I) in order to establish the importance of relativistic effects for increasing atomic number of the halogen atom. The same theoretical approach was implemented within density functional theory (DFT) by Malkina et al 9 in order to discuss the absolute NMS scale of 119 Sn.…”
Section: Introductionmentioning
confidence: 99%